Gintonin stimulates gliotransmitter release in cortical primary astrocytes - Kim, Hyunsook; Lee, Byung-Hwan; Choi, Sun-Hye; Kim, Hyeon-Joong; Jung, Suk-Won; Hwang, Sung-Hee; Rhim, Hyewon; Kim, Hyung-Chun; Cho, Ik-Hyun; Nah, Seung-Yeol (ELSEVIER IRELAND LTD, 2015)
Lysophosphatidic acid (LPA) is a simple and minor phospholipid, but serves as a lipid-derived neurotransmitter via activation of G protein-coupled LPA receptors. Astrocytes abundantly express LPA receptors and contain gliotransmitters that modulate astrocyte-neuron interactions. Gintonin is a novel ginseng-derived G protein-coupled LPA receptor ligand. Gintonin induces [Ca2+](i) transients in neuronal and non-neuronal cells via activation of LPA receptors, which regulate calcium-dependent ion channels and receptors. A line of evidence shows that neurotransmitter-mediated [Ca2+](i) elevations in astrocytes are coupled with gliotransmitter release. However, little is known about whether gintonin-mediated [Ca2+](i) transients are coupled to gliotransmitter release in astrocytes. In the present study, we examined the effects of gintonin on adenosine triphosphate (ATP) and glutamate release in mouse cortical primary astrocytes. Application of gintonin to astrocytes induced [Ca2+](i) transients in a concentration-dependent and reversible manner. However, ginsenosides, other active ingredients in ginseng, had no effect on [Ca2+](i) transients. The induction of gintonin-mediated [Ca2+](i) transients was attenuated/blocked by the LPA1/3 receptor antagonist Ki16425, a phospholipase C inhibitor, an inositol 1,4,5-triphosphate receptor antagonist, and an intracellular Ca2+ chelator. Gintonin treatment on astrocytes increased ATP and glutamate release in a concentration- and time-dependent manner. BAPTA and Ki16425 attenuated gintonin-mediated ATP and glutamate release in astrocytes. The present study shows that gintonin-mediated [Ca2+](i) transients are coupled to gliotransmitter release via LPA receptor activation. Finally, kintonin-mediated [Ca2+](i) transients and gliotransmitter release from astrocytes via LPA receptor activation might explain one mechanism of gintonin-mediated neuromodulation in the central nervous system. (C) 2015 Elsevier Ireland Ltd. All rights reserved.
Keywords: LYSOPHOSPHATIDIC ACID RECEPTOR; GINSENG; PROTEIN; INVOLVEMENT; ACTIVATION; GLUTAMATE; SYNAPSE; LIGAND